Prevalence and factors associated with group B streptococcal colonization in pregnant women - Taís Viana Lédo de Oliveira; Fabrícia Almeida Fernandes Santana; Claudio Lima Souza; Márcio Vasconcelos Oliveira (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to estimate the prevalence and the factors associated with the colonization by group B streptococcus (GBS) in pregnant women from the urban area attended at health units in a municipality in northeastern Brazil. Methods: it is a cross-sectional study conducted from January 2017 to March 2018. Vagino-rectal swabs were collected from 210 pregnant women between 32 and 40 weeks of gestation. The swabs were seeded on 5% sheep blood agar and on chromogenic agar. For confirmatory identification of GBS, the CAMP test and latex agglutination were used. Descriptive analysis and univariate and multivariate association analysis were performed using a multinomial logistic model. Results: the prevalence of GBS colonization among pregnant women was 18.1% (n = 38), and a statistically significant association (p<0.05) was found for income and parity variables in the group of older women in the univariate analysis, and for skin color, age and parity in the final multivariate analysis. Conclusions: the prevalence of maternal colonization by GBS was similar to that described in other studies. Although some risk factors, such as skin color, age and parity, were associated with colonization, other studies are essential to establish more information on pregnant women more likely to be colonized by GBS.